The analysis of naturally occurring radionuclides in different objects of the environment in the Republic of Belarus - Eroshov, Anatol I.; Martsul, Ivan N.; Antonenkov, Alexandr I. (Journal of the Belarusian State University. Ecology, 2019)
The study analyses naturally occurring Radium-226 and Thorium-232 and Potassium-40 in the soils of various textural content and some crops and materials used in construction. The study reveals in what forms these naturally occurring radionuclides are presented; also the effective activity content for some construction materials has been estimated.